Effect of Post-Annealing Treatment on the Morphological and Optical Properties of ZnO Thin Film Fabricated by Spraying Deposition Method - Teguh Darsono; Muqoyyanah Muqoyyanah; Sulhadi Sulhadi; Siti Wahyuni; Putut Marwoto; Sugianto Sugianto (Department of Physics, Sebelas Maret University, 2021)
This work investigated the effect of post-annealing treatment on the fabrication of zinc oxide (ZnO) thin film by spraying deposition method. Based on SEM analysis, the annealed ZnO thin film at 400˚C presented better uniformity as compared to the non-annealed film. Further measurement by UV-Vis revealed that the lowest optical band gap energy (Eg) (3.22 eV) was achieved by 400˚C sample. These results confirmed that post-annealing treatment enhanced the optical and morphological properties of the fabricated ZnO thin film.